Towards full-fledged inflation targeting monetary policy regime in Mauritius - Ashwin Madhou; Tayushma Sewak; Imad A. Moosa; Vikash Ramiah; Florian Gerth (Journal of Risk and Financial Management, 2021)
An increasing number of emerging and developing countries have adopted or are transitioning towards full-fledged inflation targeting (FFIT) as the main monetary policy framework to anchor inflation. In this paper, we explore the FFIT regime as a means for Mauritius to achieve stable inflation, anchor inflationary expectations and establish credibility in committing monetary policy towards price stability as its primary goal. This paper reviews and highlights issues experienced with the current monetary policy framework and the challenges in transitioning towards FFIT. Given that forecasting is central to FFIT, we develop a practical model-based forecasting and policy analysis system (FPAS) to support transition to FFIT, taking into account structural features and shocks that are specific to the Mauritius economy.
Keywords: C51; E31; E37; E52; F47; O23; 330; forecasting; inflation targeting; Mauritius; monetary transmission mechanism